U.S. Military Strategy Since Vietnam - John Mueller (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2023)
Impelled by an overwhelming desire to hunt down those responsible for the September 11, 2001, terrorist attacks, the United States launched military invasions of Afghanistan and Iraq where it toppled regimes that had little or nothing to do with 9/11. There has been a tendency to see these exercises as misguided elements of a coherent plan to establish a “liberal world order” or to apply “liberal hegemony.” In fact however, the militarization of the post-9/11 period has been a glaring, extended, and highly consequential aberration. During the quarter century before that, the United States pursued a foreign policy that was far more restrained militarily, and it seems ready now to resume that tradition after its exhausting 9/11-induced military ventures which have so thoroughly failed to deliver satisfactory results at an acceptable cost. Moreover, public opinion in the United States it is not messianic or in constant search of monsters abroad to destroy. As part of its move back to a more restrained military policy, the United States developed—or further developed—a strategy called “by, with, and through” that was particularly evident in its successful military campaign from 2014 to 2019 against the Islamic State. In this, the United States worked with local forces by providing advice, supplies, and intelligence, and carrying out airstrikes while the locals were expected to take almost all of the casualties. Although hardly new, this approach seems to have a future and is currently being applied in the war in Ukraine.